On the Nature of Banks. (15th March 2019) - Angeles, Luis
Summary: Two views exist regarding the nature of the banking business. The dominant view defines banks as financial intermediaries – institutions in the business of transferring money from savers to borrowers. An alternative view advances that banks finance borrowers via money creation. I explain the differences between these two views and argue for the superiority of the latter one as a description of modern banking. I discuss the implications for economic analysis and explain how the connection between bank lending and money creation helps us understand the effects of banking on economic activity.